2008
DOI: 10.1180/minmag.2008.072.3.799
|View full text |Cite
|
Sign up to set email alerts
|

Gemmological investigation of a synthetic blue beryl: a multi-methodological study

Abstract: A multi-methodological investigation of a synthetic Cu/Fe-bearing blue beryl [IV(Be2.86Cu0.14)∑=3.00VI(Al1.83Fe3+0.14Mn2+0.03Mg0.03)∑=2.03IV(Si5.97Al0.03∑=6.00O18.(Li0.12Na0.04.0.40H2O)] has been performed by means of gemmological standard testing, electron microprobe chemical analyses, laser ablation inductively coupled plasma mass spectroscopy, thermo-gravimetric analyses, infrared spectroscopy and single-crystal X-ray diffraction in order to determine the gemmological properties, crystal structure and cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…It must be noted that, although the extensive literature on beryl (e.g., Nassau 1967, 1968;Charoy et al 1996) shows that the ν 3 mode of doubly coordinated H 2 O [II] typically occurs in the form of a broad absorption (FWHM, full width at half maximum height in the range 50-70 cm −1 , e.g., Adamo et al 2008), the FWHM of the 3665 cm −1 band in Fig. 3a is much larger (~150 cm −1 ) than that observed for the other components.…”
Section: Experimental Methods and Studied Materialsmentioning
confidence: 99%
“…It must be noted that, although the extensive literature on beryl (e.g., Nassau 1967, 1968;Charoy et al 1996) shows that the ν 3 mode of doubly coordinated H 2 O [II] typically occurs in the form of a broad absorption (FWHM, full width at half maximum height in the range 50-70 cm −1 , e.g., Adamo et al 2008), the FWHM of the 3665 cm −1 band in Fig. 3a is much larger (~150 cm −1 ) than that observed for the other components.…”
Section: Experimental Methods and Studied Materialsmentioning
confidence: 99%
“…Except for stoppaniite Be 3 Fe 3+ 2 Si 6 O 18 (e.g., Ferraris et al 1998, Della Ventura et al 2007, Fe 2+ always significantly predominates over Fe 3+ in the beryl-group minerals (e.g., Aurisicchio et al 1988, Viana et al 2002, Braga et al 2002, da Costa et al 2006, Adamo et al 2008, Groat et al 2010, Novák & Filip 2010.…”
Section: Introductionmentioning
confidence: 97%
“…To date, several studies have been carried out on the crystal-chemistry behavior of beryls and devoted to determining the position and orientation of water molecule inside the channels of the structure with a wide variety of extra-framework populations (Wood and Nassau 1968;de Almeida Sampaio Filho et al 1973a, b;Goldman et al 1978;Aines and Rossman 1984;Barton 1986;Brown and Mills 1986;Čemić et al 1986;Hazen et al 1986;Aurisicchio et al 1988;Sheriff et al 1991;Artioli et al 1993;Charoy et al 1996;Kolesov and Geiger 2000;Pankrath and Langer 2002;Andersson 2006;Gatta et al 2006;Adamo et al 2008). However, there are few reports in the literature about the elasticity of beryl at high pressure (Yoon and Newnham 1973;Hazen et al 1986;Prencipe and Nestola 2005;Qin et al 2008), especially for the thermoelasticity of beryl at simultaneously high pressure and high temperature (Prencipe et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The stacking of the sixfold ring gives rise to open channels that aligned along the c-axis (Gibbs et al 1968). Previous studies on composition and structure have shown that the open channels in the beryl structure can accommodate water molecules as well as alkali cations (Gibbs et al 1968;de Almeida Sampaio Filho et al 1973a, b;Hawthorne and Černý 1977;Goldman et al 1978;Aines and Rossman 1984;Brown and Mills 1986;Adamo et al 2008). The presence of alkali cations is generally ascribed to the balance on the deficiency of positive charges, resulting from the replacement of octahedral Al and tetrahedral Be by cations of lower valence, such as Fe 2+ , Mn 2+ , Mg 2+ , and Li + .…”
Section: Introductionmentioning
confidence: 98%